Animated Soviet Propaganda From the October Revolution to Perestroika - Ivanov-Vano, Ivan Petrovic; Atamanov, Lev Konstantinovic; Vertov, Dziga (Jove, 2006)
From 1924 to perestroika the USSR produced more than 4 dozen animated propaganda films. They weren't for export. Their target was the new nation and their goal was to win over the hearts and minds of the Soviet people. Anti-American, Anti-British, Anti-German, Anti-Capitalist, Anti-Fascist, some of these films are as artistically beautiful as the great political posters made after the 1917 revolution which inspired Soviet animation. A unique series. With a unique perspective. Includes interviews with the directors of the animated films which are still alive and commentary by a leading Soviet film scholar. [www.russiananimation.com]